Localized Crystal‐Storing Histiocytosis Presenting as a Breast Nodule: An Unusual Presentation of a Rare Entity. Issue 5 (17th July 2014) - Chaudhary, Shweta; Navarro, Maria; Laser, Jordan; Berman, Evan; Bhuiya, Tawfiqul
Abstract Crystal‐storing histiocytosis (CSH) is a rare disorder associated with crystalline immunoglobulin deposition in the cytoplasm of histiocytes and is usually associated with lymphoproliferative or plasma cell disorders (LP‐PCD) that express monoclonal immunoglobulin. Localized CSH without underlying LP‐PCD are extremely rare. We report a case of localized CSH in breast which was an unexpected difficult diagnosis. The awareness of this entity is of importance to delineate it morphologically from other common differential diagnosis and enable appropriate management. To date, this is the first case of localized CSH reported in breast in a patient with no known history of LP‐PCD.